ALGORITMA PENENTUAN TITIK PENCEKAMAN HOLE-BASED MODULAR FIXTURE - Josef Hernawan Nudu; Isa Setiasyah Toha (Institute of Research and Community Outreach - Petra Christian University, 2008)
This article illustrates fixturing algorithm for determining clamping point of hole-based modular fixture. The proposed algorithm is based on the algorithm developed by Ariastuti et al. The previous algorithm could be applied for determining clamping point of dedicated or slot-based modular fixture but it can not be applied directly for hole-based modular fixture. Conversion of locators’ coordinate and clamping coordinate into coincident baseplate-coordinates and an approach for modeling the magnitude and action point of equivalent forces are proposed. This algorithm is designed for fixturing prismatic workpart having machining feature(s) being processed on a vertical milling machine. The machining features are hole, blind hole, pocket, slot, blind slot, step, and blind step. Three hypothetical worksamples were analyzed using Ariastuti’s algorithm and this new algorithm. The result shows that both algorithms have the same properties in terms of feasible fixturing and unfeasible fixturing on a single setup.The new algorithm gives coordinates that coincide with holes of related baseplate in feasible fixturing. Forces equilibrium during machining is the only aspect being considered for feasibity analysis. Fixture elements’ dimension, strength, and deformation have not been considered yet. Abstract in Bahasa Indonesia: Makalah ini memaparkan algoritma fixturing untuk penentuan titik pencekaman fixture modular jenis hole yang dikembangan dari algoritma Ariastuti et al. Algoritma Ariastuti et al. dapat digunakan untuk menentukan titik pencekaman dedicated fixture dan modular fixture jenis slot, namun tidak dapat diterapkan secara langsung pada modular fixture jenis hole. Algoritma usulan menambahkan satu tahapan berupa penyesuaian koordinat lokator dan klem yang bersesuaian dengan posisi lubang pada plat dasar modular fixture jenis hole. Algoritma yang diusulkan berbeda dalam hal penentuan besar dan titik tangkap gaya potong ekivalen, serta penentuan titik pencekaman yang dipilih. Penelitian dibatasi pada fixturing benda kerja prismatik yang memiliki feature hole, blind hole, pocket, slot, blind slot, step, dan blind step untuk pemesinan pada mesin milling vertikal. Fisibilitas fixturing ditentukan oleh kondisi kesetimbangan gaya selama proses pemesinan. Aplikasi algoritma usulan pada tiga buah benda uji hipotetis memberikan hasil yang setara dengan algoritma Ariastuti et al.; berupa kondisi fixturing fisibel atau tidak fisibel. Hasil kondisi fixturing yang fisibel adalah titik lokator dan klem yang bersesuaian dengan posisi susunan lubang pada plat dasar fixture modular untuk pemesinan benda kerja dalam satu kali setup. Algoritma yang dikembangkan belum mempertimbangkan kendala dimensi dan kekuatan elemen fixture serta deformasi. Kata kunci: fixture modular, fixturing, titik pencekaman